Comparison Analysis of Open and Closed Proportional Election Systems in the Perspective of State Law in Indonesia - Samantha Elizabeth Fitzgerald; Nathanael Telaumbanua; Rasji Rasji (CV. Rayyan Dwi Bharata, 2023)
The development of elections in Indonesia has two systems, namely, closed proportional system and open proportional system. Both electoral systems have their own advantages and disadvantages. The implementation of both electoral systems has significant legal and political implications in the context of state law in Indonesia. This background explanation illustrates the existence of legal problems related to the electoral system in Indonesia and the legal implications of the application of each electoral system. The research used in this research is a combination of conceptual approach with comparative approach. The comparative analysis of open and closed proportional electoral systems in the perspective of state laws in Indonesia is conducted. It can be concluded that the implementation of an open or closed system cannot be viewed as a single solution to all legal problems in the country. Decisions on the most suitable electoral system for Indonesia must consider aspects of democracy, political participation, justice, and political stability. The selection of the right electoral system will have significant implications in building a democratic and effective political system.